Fibre Reinforced Polymer (FRP) connectors for Steel Fibre Reinforced Self-Compacting Concrete (SFRSCC) sandwich panels - Lameiras, Rodrigo Melo (2012)
Insulated sandwich wall panels are frequently composed of external concrete layers, mechanically connected through metallic connectors, such as trusses. Due to their high thermal conductivity, these connectors generally cause thermal bridges on the building envelope. In view of this problem, an innovative system is proposed where FRP connectors are used together with a thermal insulation layer. Steel Fibre Reinforced Self-Compacting Concrete (SFRSCC) wythes are also used to obtain panels that are both technically and economically advantageous. However, to present day there is no experimental data on the mechanical behaviour of the suggested connections. In this research, an experimental study is performed to characterize different types of FRP-SFRSCC connections under pull-out tests. Shear connection behaviour under monotonic loading is evaluated with slip controlled tests. Embedded and adhesively bonded connection solutions between SFRSCC layers and FRP connectors are studied.